Decolonization and Healing: indigenous Experiences in the United States, New Zealand, Australia and Greenland - Linda Archibald (Aboriginal Healing Foundation, 2006)
A study of Indigenous decolonization and healing in the United States, New Zealand, Australia and Greenland